Pembatasan Penerapan Restorative Justice dalam Perkara Kekerasan Seksual pada Tahap Penyelidikan dan Penyidikan dari Perspektif Viktimologi (Kajian Berdasarkan KUHAP Baru dan UU TPKS) - Yogie Fahrisal; Benny Irawan; Muttaqin Muttaqin (Universitas Sultan Ageng Tirtayasa, 2026)
This study analyzes the limitation of Restorative justice in sexual violence cases at the preliminary investigation and criminal investigation stages from a victimology perspective based on the new Criminal Procedure Code and the TPKS Law. The issue is important because the new Criminal Procedure Code provides space for Restorative justice, while sexual violence cases have a special character related to trauma, power relations, social pressure, and the risk of revictimization. This study uses normative legal methods with analytical-prescriptive properties through statutory, conceptual, victimological, and secondary-document-based case approaches. The results show that Restorative justice in sexual violence cases cannot be used as a mechanism to stop cases against adult perpetrators. Article 23 of the TPKS Law and Article 82 letter d of the new Criminal Procedure Code restrict the settlement of sexual violence cases outside the judicial process. The revocation of the victim's report also does not automatically remove the adequacy of evidence, because investigators remain obliged to assess the victim's voluntariness and trace other relevant evidence. This research confirms that the police have a responsibility to prevent the abuse of Restorative justice through victim-oriented examinations, risk assessments, mentoring, identity protection, and cross-agency coordination. Thus, Restorative justice in sexual violence cases must be placed as a victim-recovery paradigm, not as a shortcut to stop the case.